Emerging trends in domestic homicide/femicide in Greece over the period 2010–2021. (April 2023) - Karakasi, Maria-Valeria; Voultsos, Polychronis; Fotou, Eleni; Nikolaidis, Ioannis; Kyriakou, Maria Sofia; Markopoulou, Maria; Douzenis, Athanasios; Pavlidis, Pavlos
Temporal trends in epidemiological parameters of domestic homicide and femicide in Greece over the last decade have not yet been studied. We conducted this study to fulfill this purpose. Specifically, we conducted a retrospective epidemiological study using 11-year data from the official nationwide Hellenic Police Archives and statistically analyzed data regarding domestic homicide and femicide. Overall, 1370 records of homicides among which 236 domestic homicides were identified. The pattern emerging from the statistical results of the present study highlighted the phenomenon of femicide as the gravest current issue to be interpreted and addressed. Nationally, the average number of homicides was 114.2/year, among which 19.7 domestic homicides. However, in 2021, while a decrease was recorded in homicides in general to 89 incidents per year, domestic homicides skyrocketed to 34 cases, reaching the highest annual number ever nationally recorded. On average, domestic homicides account for 18.2% of all homicides in Greece. In 2021, however, this percentage rose to 38.2%. The number of male victims of domestic homicide has declined over the years, with a further decline in 2021, in stark contrast to the number of women escalating over time and even more sharply in 2021. The proportion of female victims of domestic homicides in Greece was fourfold higher on average. The fact that cases of domestic homicide and femicide have received a lot of media attention, the recent Greek financial crisis, as well as increased alcohol and drug consumption due to the COVID-19 pandemic constitute possible aggravating factors.